FIRST REPORT: EXISTENCE OF ALPHEID SHRIMP (Alpheus lobidens De Haan 1849) IN MANGROVE ECOSYSTEM OF KUALA LANGSA, ACEH, INDONESIA - Helmi Akbar; Teuku Muhammad Faisal Faisal; Siti Komariah; Andika Putriningtias; Muhammad Fauzan Isma; Syamsul Bahri; Iswahyudi Iswahyudi; Amal Saber Abdel-Rahman; Esraa Elsaeed Ibrahim Ammar; Muhammad Arif Nasution (Universitas Teuku Umar, 2021)
AbstractThe existence of alpheid shrimp species in Indonesia is not too much found in the latest scientific publications. Alpheid shrimp species can be used as an indicator to assess the quality of the environment in mangrove areas. The discovery of shrimp species from the Alpheid group adds to the list of biodiversity in the mangrove area of Kuala Langsa. Biodiversity of a high number of species in this group of shrimp is usually found in mangrove areas with muddy sand beaches. This is because, this type of shrimp has a habit of living in muddy areas. The living zone of this type of shrimp is almost the same location as the type of crab that is wrapped like the Scylla serrata group. Mangrove area kuala langsa although it has mangrove biodiversity that is relatively high. Kuala Langsa mangrove forests are dominated by the Rhizoporaceae group, which is a type of vegetation that is effective as a sediment trap from the direction of the river estuary while holding abrasion from the direction of the sea. In the current year there is also a condition of decrease in the number of large trees. This is caused by the harvest of mangrove wood to produce charcoal for fuel purposes. This condition will slowly make the function of the ecosystem decrease. Where the role of ecosystems provide living niches for aquatic organisms is decreasing. Land clearing of certain areas of the mangrove area for physical infrastructure purposes such as the construction of restaurants, settlements, roads, small aircraft runways, reduces the ability of the region to maintain the function of its ecosystem. The next thing is the ecological pressure for aquatic biota that has living niches in mangrove areas.Keyword: alpheid shrimp, alpheus, mangrove, ecosystem, kuala langsa, aceh